Production Starch Using the Yeast (Cryptococcus neoformans HTM1 Strain) Isolated From Tea (Camellia sinensis) - Dincer, Barbaros; Haciosmanoglu, Emine; Kizil, Demet; Alpay Karaoglu, Sengul (Wiley-V C H Verlag Gmbh, 2025)
Starch is a staple food in human and animal nutrition as well as a widely used raw material in industry. This study determined the capacity of producing starch of a new yeast culture, which was defined as Cryptococcus neoformans HTM1 strain by a definitive molecular diagnosis method and isolated from tea (Camellia sinensis). The produced starch was identified as wheat starch. It was established that the HTM1 strain produced 0.23 mg/mL starch with glucose, 0.30 mg/mL with fructose, and 0.37 mg/mL with sucrose. The HTM1 strain can produce starch in media with honey and waste fruit juices; the amounts of starch were calculated as 1.2 mg/mL from honey, 1.1 mg/mL from pomegranate, 0.8 mg/mL from apple, 0.9 mg/mL from tangerine, and 0.8 mg/mL from kiwi. In conclusion, in this study, it was determined that the yeast strain C. neoformans HTM1 isolated from tea can produce starch and has the potential to produce starch in vitro regardless of environmental conditions.
Keywords: Cryptococcus neoformans; production starch; tea; yeast